Anti-oxidation and anti-erosion aluminum-zirconium-carbon sliding plate for metallurgical flow control and preparation method thereof
By using zirconia coated nano-alumina fibers, polycarbonsilane powder, composite bonding curing agents and composite antioxidants in aluminum-zirconium carbon skateboards, the problems of poor oxidation and corrosion resistance of existing skateboards are solved, and the high temperature strength, thermal shock resistance and oxidation resistance of oxidation and corrosion resistance are improved, extending the service life and improving the safety and quality of the steelmaking process.
Patent Information
- Application Number
- CN202510074386.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing low-carbon aluminum-zirconium carbon skateboards for metallurgical flow control have poor oxidation and corrosion resistance during use, resulting in short service life and possible steel leakage, affecting the safety and quality of steelmaking.
Using zirconia coated nano-alumina fibers, polycarbosilane powder, composite bonding curing agents and composite antioxidants, aluminum-zirconium carbon skateboards with high temperature strength, thermal shock resistance and excellent oxidation and corrosion resistance are prepared through high-temperature sintering technology.
It has achieved significant improvements in the high temperature strength, thermal shock resistance and oxidation resistance of the skateboard, extending its service life, and improving the safety and quality of the steelmaking process.
Smart Images

Figure BDA0005246620630000031 
Figure BDA0005246620630000071 
Figure BDA0005246620630000101
Abstract
Description
Technical Field
[0001] The invention relates to an oxidation-resistant and corrosion-resistant aluminum-zirconium-carbon slide plate for metallurgical flow control and a preparation method thereof, belonging to the technical field of refractory materials. Background Art
[0002] In the process of metallurgical steelmaking, the slide plate is one of the key functional components in the sliding nozzle system, which has the function of injecting molten steel and regulating flow. It is subjected to the scouring, wear and erosion of the molten steel and the erosion of the environmental medium during use, and the use conditions are harsh. Therefore, the slide plate is required to have high high temperature strength, excellent thermal shock resistance and corrosion resistance. At present, the slide plates mainly include Al2O3-C, Al2O3-ZrO2-C, MgO-C, and medium and low temperature treated or unfired Al-Si composite low carbon Al2O3-C. Among them, Al2O3-ZrO2-C slide plates have relatively good adaptability to different steel grades and are often used in casting calcium treated steel and high manganese steel. This is mainly because the Al2O3-ZrO2-C slide plates use low expansion zirconium mullite, zirconium corundum or zirconium oxide raw materials. ZrO2 has excellent corrosion resistance. Its crystal transformation at high temperature produces a volume effect, which generates microcracks inside the material, and has the effects of phase change toughening and microcrack toughening, which can significantly improve the material's thermal shock resistance. The antioxidant Si therein generates whisker-like SiC, Si3N4, etc. when sintered in high-temperature carbon buried or N2 atmosphere, which has a reinforcing and toughening effect on the material and is beneficial to the miniaturization of the material structure, thereby improving the high-temperature performance of the Al2O3-ZrO2-C skateboard.
[0003] With the advancement of metallurgical steelmaking technology, the proportion of calcium-treated steel smelting has increased year by year. Traditional Al2O3-ZrO2-C slide plates are not resistant to oxidation and are prone to abnormal corrosion and melting loss when casting calcium-treated steel, which not only reduces the service life, but also may cause steel leakage, posing a hidden danger to steelmaking safety. Therefore, improving the oxidation resistance and corrosion resistance of Al2O3-ZrO2-C slide plates is very critical to the safe and high-quality production of the metallurgical steelmaking industry.
[0004] Chinese patent CN113880562A discloses a kind of aluminum zirconium carbon slide block and its production method combined with organic silicon resin containing nickel aluminum alloy and fired at high temperature. The raw materials are composed of 50-65% corundum, 15-30% fused zirconium corundum, 6-12% active alumina powder, 1-3% monoclinic zirconium oxide, 1-2% metallic silicon powder, 1-3% carbon black, 1-2% carbon-containing resin powder, 0.5-1% boron carbide, and 3-4% organic silicon resin and 0.2-1% nickel aluminum alloy powder in total of the above raw materials. The aluminum zirconium carbon slide block obtained by this patent has good thermal shock resistance, but poor oxidation and corrosion resistance.
[0005] Chinese patent CN106699142A discloses a metal aluminum combined silicon-free low-carbon aluminum zirconium carbon slide plate for casting high manganese steel and its production method, including main materials and additives, the main materials include the following raw materials in weight percentage: 39-50% dense fused corundum, 6-10% a-alumina powder, 25-35% zirconium corundum, 4-8% silicon carbide, 4-6% metal aluminum powder, 2-6% zirconium oxide powder, 1-3% carbon black and 0.5-1% boron carbide; the additive is phenolic resin, and the weight of the additive is 4-6% of the total weight of the main material. The production method is to weigh each raw material by weight, mix evenly, and obtain mud; then press and shape, dry at 190-210℃ for 8-10h, add hoops, grind, and dry to obtain. Although the low-carbon aluminum-zirconium-carbon slide board obtained by this patent has good high-temperature flexural strength and thermal shock resistance, the patent discloses that after research and development tests, it can meet the requirements of continuous sliding for 3 to 4 times without silicon. It can be seen that the low-carbon aluminum-zirconium-carbon slide board obtained by this patent has relatively poor antioxidant and corrosion resistance and a very short service life.
[0006] From the above, we can see that the low-carbon aluminum-zirconium-carbon slide plates currently used in metallurgy still have the outstanding problem of poor oxidation and corrosion resistance. Therefore, the development of oxidation-resistant and corrosion-resistant aluminum-zirconium-carbon slide plates for metallurgical flow control has very practical use value. Summary of the invention
[0007] In view of the shortcomings of the above-mentioned prior art, the present invention provides an aluminum-zirconium-carbon slide plate for metallurgical flow control that is resistant to oxidation and corrosion and a preparation method thereof, so as to achieve the following invention objectives: to prepare an aluminum-zirconium-carbon slide plate for metallurgical flow control that has high high-temperature strength, good thermal shock resistance, excellent anti-oxidation and anti-corrosion properties, and a long service life.
[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0009] An anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control and a preparation method thereof. The raw material composition of the anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control is, in parts by weight:
[0010]
[0011] The graded dense fused corundum particles are graded in the following manner: by weight, 10 to 30 parts of particles with a particle size of 1 to 2 mm, 15 to 25 parts of particles with a particle size of 0.5 to 1 mm, 20 to 45 parts of particles with a particle size of 0.044 to 0.5 mm, and 10 to 20 parts of particles with a particle size of less than 0.044 mm;
[0012] The graded fused zirconium mullite particles are graded in the following manner: by weight, 5 to 15 parts of particles with a particle size of 1 to 2 mm, and 25 to 40 parts of particles with a particle size of 0.5 to 1 mm;
[0013] The particle size of the aluminum oxide powder is 0.5 to 6 μm;
[0014] The particle size of the zirconium oxide powder is 0.5 to 6 μm;
[0015] The particle size of the carbon black is 0.1 to 3 μm;
[0016] The particle size of the metallic silicon powder is 0.5 to 4 μm;
[0017] The particle size of the polycarbosilane powder is 0.2-1 μm, wherein the number average molecular weight of the polycarbosilane is 1000-1800 g / mol, the softening point is 180-240° C., and the ceramic yield is 50-65% at 1000° C.;
[0018] The composite adhesive curing agent is prepared by mixing liquid thermosetting phenolic resin and liquid polysilazane in a mass ratio of 30 to 80:11, and stirring the mixture into a uniform, stable and transparent liquid to obtain the composite adhesive curing agent;
[0019] The liquid thermosetting phenolic resin has a viscosity of 3600-4500 mPa·s at 25° C., a solid content of 75-85 wt %, and a free phenol content of 3-6 wt %;
[0020] The liquid polysilazane has a number average molecular weight of 900 to 1200 g / mol, a viscosity of 10 to 50 mPa·s, and a ceramic yield of 65 to 75% when cured at 800°C;
[0021] The composite antioxidant is prepared by mixing boride and nitride in a mass ratio of 4 to 9:10, placing the mixture in a ball mill, and grinding the mixture to a particle size of 0.3 to 3 μm to obtain the composite antioxidant.
[0022] The boride is one of silicon boride, calcium boride, zirconium boride and ditungsten boride;
[0023] The nitride is one of boron nitride, silicon nitride, tungsten nitride, aluminum nitride, zirconium nitride and titanium nitride;
[0024] The following are further improvements to the above technical solution:
[0025] Step 1: Preparation of zirconia-coated nano-alumina fibers
[0026] The zirconium oxychloride aqueous solution, nano-alumina fibers, and polyethylene glycol are added to a high-speed dispersion kettle, and the dispersion rate is controlled at 7000 to 9000 rpm. After high-speed dispersion for 5 to 11 hours, the dispersion rate is reduced to 1000 to 1600 rpm, and then ammonia water with a mass concentration of 12 to 25 wt% is added dropwise at a speed of 0.1 to 1.0 g / min until the pH value of the solution reaches 9 to 10 to obtain a sol, and then the stirring is stopped, and the solution is allowed to stand for aging for 38 to 55 hours to obtain a gel, and then the gel is Wash with deionized water for 3 to 5 times, the mass of deionized water used for each washing is twice the mass of the gel, then wash with anhydrous ethanol for 2 to 4 times, the mass of anhydrous ethanol used for each washing is equal to the mass of the gel, then place the gel in a dry and dust-free room temperature environment for 90 to 130 hours, then dry it at 90 to 100° C. for 11 to 22 hours, and after cooling to room temperature in a dry environment, grind the dried gel into a powder of 600 to 1000 meshes to obtain zirconium oxide-coated nano-alumina fibers;
[0027] The zirconium oxychloride aqueous solution, wherein the mass fraction of zirconium oxychloride is 16 to 37 wt %;
[0028] The diameter of the nano-alumina fiber is 10-100 nm, and the length is 70-420 nm;
[0029] The number average molecular weight of the polyethylene glycol is 350 to 850 g / mol;
[0030] The mass ratio of the zirconium oxychloride aqueous solution, nano-aluminum oxide fibers and polyethylene glycol is 80-160:15-45:0.1-0.8.
[0031] Step 2: Preparation of aluminum zirconium carbon slide plate
[0032] According to the raw material composition of the anti-oxidation and anti-corrosion aluminum-zirconium-carbon skateboard for metallurgical flow control, various raw materials are weighed in parts by weight, and alumina powder, zirconium oxide powder, carbon black, metal silicon powder, zirconium oxide coated nano alumina fiber, polycarbosilane powder, and composite antioxidant are first put into a high-speed mixer, and the stirring rate is controlled at 130-200 rpm. After stirring and mixing for 1-2.5 hours, a mixed powder is obtained and set aside, and then graded dense fused corundum particles and graded fused zirconium mullite particles are added to a wet mill. After mixing evenly, a composite adhesive curing agent is added to the wet mill. After the composite adhesive curing agent is evenly coated on the particles, the mixed powder is added and kneaded for 1-2 hours. After 1.5 hours, the molding clay is obtained, and the clay is left to stand for 40 to 50 hours in an environment of 20 to 35°C and a relative air humidity of 30 to 50%, and then pressed into shape to obtain a skateboard brick blank. The brick blank is then dried in a tunnel drying kiln at a temperature of 170 to 200°C for 48 to 56 hours. It is then heated to 1100 to 1400°C at a heating rate of 20 to 35°C / h in a nitrogen atmosphere and fired at a constant temperature of 42 to 55 hours. After firing, it is naturally cooled to room temperature and then subjected to five steps of oil impregnation, roasting, steel hoop wearing, grinding, and coating to obtain an anti-oxidation and anti-corrosion aluminum-zirconium-carbon skateboard for metallurgical flow control.
[0033] Compared with the prior art, the present invention achieves the following beneficial effects:
[0034] 1. The present invention improves the compressive strength and flexural strength of the skateboard by adding nano-alumina fibers. Since the nano-alumina fibers have very excellent high-temperature mechanical properties, they can still maintain the original aspect ratio during the sintering process of the skateboard, and maintain their inherent excellent mechanical properties at high temperatures. At the same time, in order to enhance the original bonding force between the nano-alumina fibers and the skateboard matrix during sintering, the present invention coats a layer of highly active zirconium oxide on the surface of the alumina fibers by a gel sol method, which can promote the sintering and curing strength of the nano-alumina fibers and zirconium mullite particles, zirconium oxide powder, metal silicon powder and other raw materials, and then can give full play to the reinforcing and toughening effect of the nano-alumina fibers on the skateboard, and maximize the high-temperature mechanical properties of the skateboard;
[0035] 2. The polycarbosilane powder added in the present invention mainly plays two roles. First, the polycarbosilane powder will melt into a liquid with high viscosity and strong adhesion at 200-400°C, which will greatly promote the bonding between the raw material powder particles of the skateboard, promote the densification of the sintering process, and make the particles sintered more densely into a whole, thereby improving the various mechanical properties of the skateboard. Second, polycarbosilane has a ceramic effect, and silicon carbide is generated after high-temperature sintering. The mechanical properties of silicon carbide are extremely excellent. This ceramic effect will make up for the problem of excessive porosity caused by the sintering process of phenolic resin, and promote a significant improvement in the overall mechanical properties of the skateboard.
[0036] 3. The composite adhesive curing agent composed of liquid thermosetting phenolic resin and liquid polysilazane designed by the present invention can play the role of curing and molding adhesive powder and granular materials, wherein the liquid thermosetting phenolic resin has a low cost and a high residual carbon rate, and can provide carbon elements for the skateboard matrix. The liquid polysilazane has a very high ceramic yield during the high-temperature sintering process, and can promote the overall density of the skateboard during its own ceramicization process, reduce the apparent porosity, and thus improve the mechanical properties and anti-oxidation and anti-corrosion properties of the skateboard;
[0037] 4. The present invention uses borides and nitrides with extremely high melting points and particularly good high-temperature stability to compound a composite antioxidant. These borides and nitrides can resist the strong oxidation and strong corrosion of high-temperature liquid flow in the metallurgical process, thereby increasing the service life of the slide plate;
[0038] 5. The anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control obtained by the present invention has a volume density of 3.22 to 3.30 g·cm -3 , apparent porosity 2.97~3.05%, compressive strength 246~255MPa, flexural strength 19.7~20.9MPa, thermal expansion coefficient 0.8~0.9%, continuous sliding times 5~6 times. DETAILED DESCRIPTION
[0039] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0040] Example 1: A method for preparing an anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control
[0041] Step 1: Preparation of zirconia-coated nano-alumina fibers
[0042] Add zirconium oxychloride aqueous solution, nano alumina fiber and polyethylene glycol into a high-speed dispersion kettle, control the dispersion rate at 8000 rpm, and after high-speed dispersion for 9 hours, reduce the dispersion rate to 1300 rpm, then drip ammonia water with a mass concentration of 20wt% at a speed of 0.6g / min until the pH value of the solution reaches 9.6 to obtain a sol, then stop stirring, stand and age for 45 hours to obtain a gel, then wash the gel with deionized water for 4 times, the mass of deionized water used for each washing is twice the mass of the gel, then wash it with anhydrous ethanol for 3 times, the mass of anhydrous ethanol used for each washing is equal to the mass of the gel, then put the gel in a dry and dust-free room temperature environment and let it air for 120 hours, then put it in 96°C and dry it for 15 hours, after cooling to room temperature in a dry environment, grind the dried gel into a 900-mesh powder to obtain zirconium oxide-coated nano alumina fiber;
[0043] The zirconium oxychloride aqueous solution, wherein the mass fraction of zirconium oxychloride is 19wt%;
[0044] The diameter of the nano-alumina fiber is 60nm and the length is 300nm;
[0045] The number average molecular weight of the polyethylene glycol is 600 g / mol;
[0046] The mass ratio of the zirconium oxychloride aqueous solution, nano-aluminum oxide fibers, and polyethylene glycol is 130:30:0.7.
[0047] Step 2: Preparation of aluminum zirconium carbon slide plate
[0048] The raw material composition of the oxidation-resistant and corrosion-resistant aluminum-zirconium-carbon slide plate for metallurgical flow control is, in parts by weight:
[0049]
[0050] The graded dense fused corundum particles are graded in the following manner: by weight, 25 parts of particles with a particle size of 1.5 mm, 22 parts of particles with a particle size of 0.8 mm, 30 parts of particles with a particle size of 0.3 mm, and 16 parts of particles with a particle size of less than 0.044 mm;
[0051] The graded fused zirconium mullite particles are graded as follows: by weight, 10 parts of particles with a particle size of 1.4 mm and 35 parts of particles with a particle size of 0.7 mm;
[0052] The particle size of the alumina powder is 1 μm;
[0053] The particle size of the zirconium oxide powder is 3 μm;
[0054] The particle size of the carbon black is 1 μm;
[0055] The particle size of the metallic silicon powder is 2 μm;
[0056] The particle size of the polycarbosilane powder is 0.6 μm, wherein the number average molecular weight of polycarbosilane is 1500 g / mol, the softening point is 200° C., and the ceramic yield is 60% at 1000° C.;
[0057] The composite adhesive curing agent is prepared by mixing a liquid thermosetting phenolic resin and a liquid polysilazane in a mass ratio of 60:11, and stirring the mixture into a uniform, stable, transparent liquid to obtain the composite adhesive curing agent;
[0058] The liquid thermosetting phenolic resin has a viscosity of 4000 mPa·s at 25° C., a solid content of 82 wt %, and a free phenol content of 4 wt %;
[0059] The liquid polysilazane has a number average molecular weight of 1000 g / mol, a viscosity of 30 mPa·s, and a ceramic yield of 72% when cured at 800°C;
[0060] The composite antioxidant is prepared by mixing boride and nitride in a mass ratio of 6:10, placing the mixture in a ball mill, and grinding the mixture to a particle size of 1 μm to obtain the composite antioxidant;
[0061] The boride is silicon boride;
[0062] The nitride is boron nitride;
[0063] According to the raw material composition of the aluminum zirconium carbon slide plate for metallurgical flow control and oxidation resistance, various raw materials are weighed in parts by weight, and alumina powder, zirconium oxide powder, carbon black, metal silicon powder, zirconium oxide coated nano alumina fiber, polycarbosilane powder, and composite antioxidant are first put into a high-speed mixer, and the stirring rate is controlled at 160 rpm. After stirring and mixing for 2 hours, a mixed powder is obtained for standby use, and then graded dense fused corundum particles and graded fused zirconium mullite particles are added to a wet mill. After mixing evenly, a composite adhesive curing agent is added to the wet mill. After the composite adhesive curing agent is evenly coated on the particles, Add the mixed powder and mix for 1.2 hours to obtain the molding clay. After the clay is allowed to stand for 46 hours in an environment at 30°C and a relative air humidity of 45%, it is pressed into shape to obtain a skateboard brick blank. The brick blank is then dried in a tunnel drying kiln at 180°C for 55 hours. Then, it is heated to 1200°C at a heating rate of 33°C / h in a nitrogen atmosphere and fired at a constant temperature for 50 hours. After firing, it is naturally cooled to room temperature and then subjected to five steps of oil impregnation, roasting, steel hoop wearing, grinding, and coating to obtain an anti-oxidation and anti-corrosion aluminum-zirconium-carbon skateboard for metallurgical flow control.
[0064] Example 2: A method for preparing an anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control
[0065] Step 1: Preparation of zirconia-coated nano-alumina fibers
[0066] Add zirconium oxychloride aqueous solution, nano-alumina fibers and polyethylene glycol into a high-speed dispersion kettle, control the dispersion rate at 7000 rpm, and after high-speed dispersion for 5 hours, reduce the dispersion rate to 1000 rpm, then drop ammonia water with a mass concentration of 12wt% at a rate of 0.1g / min until the pH value of the solution reaches 9 to obtain a sol, then stop stirring, stand and age for 38 hours to obtain a gel, then wash the gel with deionized water for 3 times, the mass of deionized water used for each washing is twice the mass of the gel, then wash it with anhydrous ethanol for 2 times, the mass of anhydrous ethanol used for each washing is equal to the mass of the gel, then put the gel in a dry and dust-free room temperature environment and let it air for 90 hours, then put it in 90°C and dry it for 11 hours, after cooling to room temperature in a dry environment, grind the dried gel into a 600-mesh powder to obtain zirconium oxide-coated nano-alumina fibers;
[0067] The zirconium oxychloride aqueous solution, wherein the mass fraction of zirconium oxychloride is 16wt%;
[0068] The diameter of the nano-alumina fiber is 10 nm and the length is 70 nm;
[0069] The number average molecular weight of the polyethylene glycol is 350 g / mol;
[0070] The mass ratio of the zirconium oxychloride aqueous solution, nano-aluminum oxide fibers and polyethylene glycol is 80:15:0.1.
[0071] Step 2: Preparation of aluminum zirconium carbon slide plate
[0072] The raw material composition of the oxidation-resistant and corrosion-resistant aluminum-zirconium-carbon slide plate for metallurgical flow control is, in parts by weight:
[0073]
[0074] The graded dense fused corundum particles are graded in the following manner: by weight, 10 parts of particles with a particle size of 1 mm, 15 parts of particles with a particle size of 0.5 mm, 20 parts of particles with a particle size of 0.044 mm, and 10 parts of particles with a particle size of less than 0.044 mm;
[0075] The graded fused zirconium mullite particles are graded as follows: by weight, 5 parts of particles with a particle size of 1 mm and 25 parts of particles with a particle size of 0.5 mm;
[0076] The particle size of the aluminum oxide powder is 0.5 μm;
[0077] The particle size of the zirconium oxide powder is 0.5 μm;
[0078] The particle size of the carbon black is 0.1 μm;
[0079] The particle size of the metallic silicon powder is 0.5 μm;
[0080] The particle size of the polycarbosilane powder is 0.2 μm, wherein the number average molecular weight of the polycarbosilane is 1000 g / mol, the softening point is 180° C., and the ceramic yield at 1000° C. is 50%;
[0081] The composite adhesive curing agent is prepared by mixing liquid thermosetting phenolic resin and liquid polysilazane in a mass ratio of 30:11, and stirring the mixture into a uniform, stable and transparent liquid to obtain the composite adhesive curing agent;
[0082] The liquid thermosetting phenolic resin has a viscosity of 3600 mPa·s at 25° C., a solid content of 75 wt %, and a free phenol content of 3 wt %;
[0083] The liquid polysilazane has a number average molecular weight of 900 g / mol, a viscosity of 10 mPa·s, and a ceramic yield of 65% when cured at 800°C;
[0084] The composite antioxidant is prepared by mixing boride and nitride in a mass ratio of 4:10, placing the mixture in a ball mill, and grinding the mixture to a particle size of 0.3 μm to obtain the composite antioxidant.
[0085] The boride is calcium boride;
[0086] The nitride is silicon nitride;
[0087] According to the raw material composition of the aluminum zirconium carbon slide for metallurgical flow control and oxidation resistance, various raw materials are weighed in parts by weight. Alumina powder, zirconium oxide powder, carbon black, metal silicon powder, zirconium oxide coated nano alumina fiber, polycarbosilane powder, and composite antioxidant are first put into a high-speed mixer, and the stirring rate is controlled at 130 rpm. After stirring and mixing for 1 hour, a mixed powder is obtained and set aside. Then, graded dense fused corundum particles and graded fused zirconium mullite particles are added to a wet mill. After mixing evenly, a composite adhesive curing agent is added to the wet mill. After the composite adhesive curing agent is evenly wrapped on the particles, , and then add the mixed powder and mix for 1 hour to obtain the clay for molding. After the clay is allowed to stand for 40 hours in an environment of 20°C and 30% relative air humidity, it is pressed into shape to obtain a skateboard brick blank. The brick blank is then dried in a tunnel drying kiln at a drying temperature of 170°C for 48 hours. Then, in a nitrogen atmosphere, the temperature is increased to 1100°C at a heating rate of 20°C / h and constant temperature fired for 42 hours. After firing, it is naturally cooled to room temperature and then subjected to five steps of oil impregnation, roasting, steel hoop wearing, grinding, and coating to obtain an anti-oxidation and anti-corrosion aluminum-zirconium-carbon skateboard for metallurgical flow control.
[0088] Example 3: Preparation method of an anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control
[0089] Step 1: Preparation of zirconia-coated nano-alumina fibers
[0090] Add zirconium oxychloride aqueous solution, nano alumina fiber and polyethylene glycol into a high-speed dispersion kettle, control the dispersion rate at 9000 rpm, and after high-speed dispersion for 11 hours, reduce the dispersion rate to 1600 rpm, then drop ammonia water with a mass concentration of 25wt% at a rate of 1.0g / min until the pH value of the solution reaches 10 to obtain a sol, then stop stirring, stand and age for 55 hours to obtain a gel, then wash the gel with deionized water 5 times, the mass of deionized water used for each washing is twice the mass of the gel, then wash it with anhydrous ethanol 4 times, the mass of anhydrous ethanol used for each washing is equal to the mass of the gel, then put the gel in a dry and dust-free room temperature environment and let it air for 130 hours, then put it in 100°C and dry it for 22 hours, after cooling to room temperature in a dry environment, grind the dried gel into a 1000-mesh powder to obtain zirconium oxide-coated nano alumina fiber;
[0091] The zirconium oxychloride aqueous solution, wherein the mass fraction of zirconium oxychloride is 37wt%;
[0092] The diameter of the nano-alumina fiber is 100 nm and the length is 420 nm;
[0093] The number average molecular weight of the polyethylene glycol is 850 g / mol;
[0094] The mass ratio of the zirconium oxychloride aqueous solution, nano-aluminum oxide fibers, and polyethylene glycol is 160:45:0.8.
[0095] Step 2: Preparation of aluminum zirconium carbon slide plate
[0096] The raw material composition of the oxidation-resistant and corrosion-resistant aluminum-zirconium-carbon slide plate for metallurgical flow control is, in parts by weight:
[0097]
[0098] The graded dense fused corundum particles are graded in the following manner: by weight, 30 parts of particles with a particle size of 2 mm, 25 parts of particles with a particle size of 1 mm, 45 parts of particles with a particle size of 0.5 mm, and 20 parts of particles with a particle size of less than 0.044 mm;
[0099] The graded fused zirconium mullite particles are graded as follows: by weight, 15 parts of particles with a particle size of 2 mm and 40 parts of particles with a particle size of 1 mm;
[0100] The particle size of the alumina powder is 6 μm;
[0101] The particle size of the zirconium oxide powder is 6 μm;
[0102] The particle size of the carbon black is 3 μm;
[0103] The particle size of the metallic silicon powder is 4 μm;
[0104] The particle size of the polycarbosilane powder is 1 μm, wherein the number average molecular weight of the polycarbosilane is 1800 g / mol, the softening point is 240° C., and the ceramic yield at 1000° C. is 65%;
[0105] The composite adhesive curing agent is prepared by mixing a liquid thermosetting phenolic resin and a liquid polysilazane in a mass ratio of 80:11, and stirring the mixture into a uniform, stable, transparent liquid to obtain the composite adhesive curing agent;
[0106] The liquid thermosetting phenolic resin has a viscosity of 4500 mPa·s at 25° C., a solid content of 85 wt %, and a free phenol content of 6 wt %;
[0107] The liquid polysilazane has a number average molecular weight of 1200 g / mol, a viscosity of 50 mPa·s, and a ceramic yield of 75% when cured at 800°C;
[0108] The composite antioxidant is prepared by mixing boride and nitride in a mass ratio of 9:10, placing the mixture in a ball mill, and grinding the mixture to a particle size of 3 μm to obtain the composite antioxidant.
[0109] The boride is zirconium boride;
[0110] The nitride is tungsten nitride;
[0111] According to the raw material composition of the aluminum zirconium carbon slide for metallurgical flow control and oxidation resistance, various raw materials are weighed in parts by weight. Alumina powder, zirconium oxide powder, carbon black, metal silicon powder, zirconium oxide coated nano alumina fiber, polycarbosilane powder, and composite antioxidant are first put into a high-speed mixer. The stirring rate is controlled at 200 rpm. After stirring and mixing for 2.5 hours, a mixed powder is obtained for standby use. Then, graded dense fused corundum particles and graded fused zirconium mullite particles are added to a wet mill. After mixing evenly, a composite adhesive curing agent is added to the wet mill. After the composite adhesive curing agent is evenly wrapped on the particles, , and then add the mixed powder and mix for 1.5 hours to obtain the clay for molding. After the clay is allowed to stand for 50 hours in an environment of 35°C and 50% relative air humidity, it is pressed into shape to obtain a skateboard brick blank. The brick blank is then dried in a tunnel drying kiln at 200°C for 56 hours. Then, in a nitrogen atmosphere, the temperature is increased to 1400°C at a heating rate of 35°C / h and constant temperature fired for 55 hours. After firing, it is naturally cooled to room temperature and then subjected to five steps of oil impregnation, roasting, steel hoop wearing, grinding, and coating to obtain an anti-oxidation and anti-corrosion aluminum-zirconium-carbon skateboard for metallurgical flow control.
[0112] Comparative Example 1: Based on Example 1, step 1, preparation of zirconium oxide coated nano alumina fibers, is not performed. In step 2, preparation of the aluminum zirconium carbon skateboard, 5 parts of zirconium oxide coated nano alumina fibers are replaced by 5 parts of alumina powder in equal amounts. The specific operation is as follows:
[0113] Step 1, preparation of zirconium oxide coated nano alumina fibers, is not performed;
[0114] Step 2: Preparation of aluminum zirconium carbon slide plate
[0115] The 5 parts of zirconium oxide coated nano alumina fibers were replaced by 5 parts of alumina powder in equal amounts, and the other operations were the same as those in Example 1.
[0116] Comparative Example 2: In step 2, in the preparation of the aluminum-zirconium-carbon skateboard, 5 parts of zirconium oxide-coated nano-alumina fibers were replaced by 5 parts of nano-alumina fibers in equal amounts. The specific operation is as follows:
[0117] Step 1, preparation of zirconium oxide coated nano alumina fibers, is not performed;
[0118] Step 2: Preparation of aluminum zirconium carbon slide plate
[0119] 5 parts of zirconia-coated nano-alumina fibers were replaced by 5 parts of nano-alumina fibers, and the other operations were the same as in Example 1;
[0120] The diameter of the nano-alumina fiber is 60nm and the length is 300nm.
[0121] Comparative Example 3: Based on Example 1, in step 2, in the preparation of the aluminum zirconium carbon slide plate, no polycarbosilane powder is added, and 1 part of polycarbosilane powder is replaced with 1 part of alumina powder in equal amounts. The specific operation is as follows:
[0122] The operation of step 1 is the same as that of embodiment 1;
[0123] Step 2: Preparation of aluminum zirconium carbon slide plate
[0124] One part of polycarbosilane powder was replaced by one part of alumina powder, and other operations were the same as in Example 1.
[0125] Comparative Example 4: Based on Example 1, in step 2, in the preparation of the aluminum-zirconium-carbon slide plate, no composite antioxidant is added, and 3 parts of the composite antioxidant are replaced by 3 parts of alumina powder in equal amounts. The specific operation is as follows:
[0126] The operation of step 1 is the same as that of embodiment 1;
[0127] Step 2: Preparation of aluminum zirconium carbon slide plate
[0128] The 3 parts of composite antioxidant were replaced by 3 parts of alumina powder in equal amounts, and the other operations were the same as in Example 1.
[0129] Comparative Example 5: Based on Example 1, in step 2, in the preparation of the aluminum-zirconium-carbon slide plate, no liquid polysilazane is added to the composite adhesive curing agent, and 8 parts of the composite adhesive curing agent are replaced by 8 parts of liquid thermosetting phenolic resin in equal amounts. The specific operation is as follows:
[0130] The operation of step 1 is the same as that of embodiment 1;
[0131] Step 2: Preparation of aluminum zirconium carbon slide plate
[0132] 8 parts of the composite adhesive curing agent were replaced by 8 parts of liquid thermosetting phenolic resin, and the other operations were the same as in Example 1.
[0133] Performance Test:
[0134] Referring to the test methods and index requirements specified in the industry standard YB / T 5049-2019 and the relevant restrictions on metallurgical slide indicators in the slide brick HBLTG-80 standard, the anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plates for metallurgical flow control obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, and 5 were tested for indicators such as bulk density, apparent porosity, room temperature compressive strength, high temperature flexural strength, thermal expansion coefficient, and continuous sliding times. The relevant test data are shown in Table 1:
[0135] Table 1
[0136]
[0137]
[0138] From the data in Table 1, it can be seen that the bulk density of Examples 1-3 is all 3.22 g·cm -3 The porosity is lower than 3.05%, the compressive strength is higher than 246MPa, the flexural strength is greater than 19.7MPa, the thermal expansion rate is less than 0.9%, and the continuous sliding times can reach more than 5 times, indicating that the anti-oxidation and anti-corrosion performance is very good; in comparative example 1, no zirconium oxide-coated nano-alumina fiber is added, and the volume density of comparative example 1 is reduced to 2.97g·cm -3, the apparent porosity increased to 3.28%, the compressive strength and flexural strength decreased significantly, and in Example 1 and 5 comparative examples, the compressive strength and flexural strength decreased to the lowest value, the thermal expansion coefficient increased to the maximum value, and the number of continuous sliding was reduced to 2 times. It can be seen that the addition of zirconia-coated nano-alumina fibers can greatly increase the volume density of the skateboard and reduce the apparent porosity, which plays a very critical role in improving the compressive strength and flexural strength of the skateboard. From the reduction of the number of continuous sliding to 2 times in Comparative Example 1, it can be clearly seen that zirconia-coated nano-alumina fibers are also very important for improving the anti-oxidation and anti-corrosion of the skateboard; Comparative Example 2 replaces the zirconia-coated nano-alumina fibers with nano-alumina fibers in equal amounts, which is very similar to the situation in Comparative Example 1. The various indicators of Comparative Example 2 also decrease significantly, but the decrease is less than that in Example 1, which shows that after coating the nano-alumina fibers with zirconia, the mechanical properties and anti-oxidation and anti-corrosion properties of the skateboard can be significantly improved; Comparative Example 3 does not add polycarbosilane powder, and replaces the polycarbosilane powder with alumina powder in equal amounts. The volume of Comparative Example 3 The density drops to the lowest value in Example 1 and 5 comparative examples, the corresponding apparent porosity increases to the highest value in Example 1 and 5 comparative examples, the compressive strength and flexural strength both decrease significantly, the thermal expansion rate increases significantly, and the number of continuous sliding times decreases to 3 times, which shows that polycarbosilane powder plays a vital role in increasing the density of the skateboard, and improves the mechanical properties and anti-oxidation and anti-corrosion by promoting the densification of the skateboard; Comparative Example 4 does not add a composite antioxidant. Except that the number of continuous sliding is reduced to 2 times, other indicators of Comparative Example 4 are basically similar to those of Example 1, which shows that the main function of adding the composite antioxidant is to improve the anti-oxidation and anti-corrosion properties of the skateboard; No liquid polysilazane is added to the composite adhesive curing agent of Comparative Example 5, only a single liquid thermosetting phenolic resin is added, the volume density of Comparative Example 5 is significantly reduced, the apparent porosity increases, the compressive strength and flexural strength decrease significantly, the thermal expansion rate increases, and the number of continuous sliding is reduced to 4 times, which shows that liquid polysilazane has a very significant effect on the density, mechanical properties and anti-oxidation and anti-corrosion properties of the skateboard.
[0139] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control, characterized in that: The raw material composition of the oxidation-resistant and corrosion-resistant aluminum-zirconium-carbon slide plate for metallurgical flow control is, in parts by weight: The graded dense fused corundum particles are graded in the following manner: by weight, 10 to 30 parts of particles with a particle size of 1 to 2 mm, 15 to 25 parts of particles with a particle size of 0.5 to 1 mm, 20 to 45 parts of particles with a particle size of 0.044 to 0.5 mm, and 10 to 20 parts of particles with a particle size of less than 0.044 mm; The graded fused zirconium mullite particles are graded in the following manner: by weight, 5 to 15 parts of particles with a particle size of 1 to 2 mm, and 25 to 40 parts of particles with a particle size of 0.5 to 1 mm; The particle size of the aluminum oxide powder is 0.5 to 6 μm; The particle size of the zirconium oxide powder is 0.5 to 6 μm; The particle size of the carbon black is 0.1 to 3 μm; The particle size of the metallic silicon powder is 0.5 to 4 μm; The particle size of the polycarbosilane powder is 0.2-1 μm, wherein the number average molecular weight of the polycarbosilane is 1000-1800 g / mol, the softening point is 180-240° C., and the ceramic yield is 50-65% at 1000° C.; The composite adhesive curing agent is prepared by mixing liquid thermosetting phenolic resin and liquid polysilazane in a mass ratio of 30 to 80:11, and stirring the mixture into a uniform, stable and transparent liquid to obtain the composite adhesive curing agent; The liquid thermosetting phenolic resin has a viscosity of 3600-4500 mPa·s at 25° C., a solid content of 75-85 wt %, and a free phenol content of 3-6 wt %; The liquid polysilazane has a number average molecular weight of 900 to 1200 g / mol, a viscosity of 10 to 50 mPa·s, and a ceramic yield of 65 to 75% when cured at 800°C; The composite antioxidant is prepared by mixing boride and nitride in a mass ratio of 4 to 9:10, placing the mixture in a ball mill, and grinding the mixture to a particle size of 0.3 to 3 μm to obtain the composite antioxidant. The boride is one of silicon boride, calcium boride, zirconium boride and ditungsten boride; The nitride is one of boron nitride, silicon nitride, tungsten nitride, aluminum nitride, zirconium nitride and titanium nitride; The zirconium oxide coated nano alumina fiber is prepared by: adding a zirconium oxychloride aqueous solution, nano alumina fiber and polyethylene glycol into a high-speed dispersion kettle, controlling the dispersion rate at 7000 to 9000 rpm, and dispersing at high speed for 5 to 11 hours, reducing the dispersion rate to 1000 to 1600 rpm, then dripping ammonia water with a mass concentration of 12 to 25 wt% at a speed of 0.1 to 1.0 g / min until the pH value of the solution reaches 9 to 10 to obtain a sol, then stopping stirring, and standing for aging for 38 to 55 hours. , obtaining a gel, then washing the gel with deionized water for 3 to 5 times, the mass of deionized water used for each washing being twice the mass of the gel, and then washing the gel with anhydrous ethanol for 2 to 4 times, the mass of anhydrous ethanol used for each washing being equal to the mass of the gel, and then placing the gel in a dry and dust-free environment at room temperature for 90 to 130 hours, and then drying it at 90 to 100°C for 11 to 22 hours. After cooling to room temperature in a dry environment, the dried gel is ground into a powder of 600 to 1000 meshes to obtain zirconium oxide-coated nano-alumina fibers.
2. The anti-oxidation and anti-corrosion aluminum-zirconium-carbon slide plate for metallurgical flow control according to claim 1, characterized in that: The zirconium oxychloride aqueous solution, wherein the mass fraction of zirconium oxychloride is 16 to 37 wt %; The diameter of the nano-alumina fiber is 10-100 nm, and the length is 70-420 nm; The number average molecular weight of the polyethylene glycol is 350 to 850 g / mol; The mass ratio of the zirconium oxychloride aqueous solution, nano-aluminum oxide fibers and polyethylene glycol is 80-160:15-45:0.1-0.
8.
3. The method for preparing the oxidation-resistant and corrosion-resistant aluminum-zirconium-carbon slide plate for metallurgical flow control according to claim 1, characterized in that: According to the raw material composition of the anti-oxidation and anti-corrosion aluminum-zirconium-carbon skateboard for metallurgical flow control, various raw materials are weighed in parts by weight, and alumina powder, zirconium oxide powder, carbon black, metal silicon powder, zirconium oxide coated nano alumina fiber, polycarbosilane powder, and composite antioxidant are first put into a high-speed mixer, and the stirring rate is controlled at 130-200 rpm. After stirring and mixing for 1-2.5 hours, a mixed powder is obtained and set aside, and then graded dense fused corundum particles and graded fused zirconium mullite particles are added to a wet mill. After mixing evenly, a composite adhesive curing agent is added to the wet mill. After the composite adhesive curing agent is evenly coated on the particles, the mixed powder is added and kneaded for 1-2 hours. After 1.5 hours, the molding clay is obtained, and the clay is left to stand for 40 to 50 hours in an environment of 20 to 35°C and a relative air humidity of 30 to 50%, and then pressed into shape to obtain a skateboard brick blank. The brick blank is then dried in a tunnel drying kiln at a temperature of 170 to 200°C for 48 to 56 hours. It is then heated to 1100 to 1400°C at a heating rate of 20 to 35°C / h in a nitrogen atmosphere and fired at a constant temperature of 42 to 55 hours. After firing, it is naturally cooled to room temperature and then subjected to five steps of oil impregnation, roasting, steel hoop wearing, grinding, and coating to obtain an anti-oxidation and anti-corrosion aluminum-zirconium-carbon skateboard for metallurgical flow control.
Citation Information
Patent Citations
Metallic aluminium and non-silicone low-carbon alumina-zirconia-carbon slide plate for pouring high manganese steel and production method thereof
CN106699142A
Aluminum-zirconium-carbon sliding plate brick prepared by combining nickel-aluminum alloy-containing organic silicon resin with high-temperature firing and production method of aluminum-zirconium-carbon sliding plate brick
CN113880562A
Cited By
Corundum refractory castable containing mullite fibers and preparation method of corundum refractory castable
CN121135392A
Corundum-based refractory castable containing mullite fibers and method for producing the same
CN121135392B